Nitric oxide, hypoxia and brain inflammation. (26th October 2004) - Mander, P.; Brown, G.C.
Abstract : NO (nitric oxide) acutely and potently inhibits mitochondrial cytochrome oxidase in competition with oxygen, thereby raising the apparent K M for oxygen of mitochondria and neurons into the physiological or pathological range. We find that NO from an NO donor or glial inducible NOS (nitric oxide synthase) highly sensitizes neurons to hypoxia-induced death, probably via the NO–oxygen competition at cytochrome oxidase. Thus the NO from neuronal NOS during excitotoxicity or the NO from inducible NOS during inflammation may sensitize the brain to hypoxic/ischaemic damage.